AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DI KECAMATAN DOLO SELATAN KABUPATEN SIGI - Irma, Ade (Katalogis, 2015)
This study aims: 1) to determine the accountability of the village fund allocation management in the sub district of South Dolo in Sigi district; 2) to determine the factors that can impact on village fund allocation in financial administration in order to meet the applicable regulations; and 3) To determine the economic benefits (empowerment) through the village fund allocation. This research was conducted in the sub district of South Dolo villages which have been implemented the village fund allocation. The number of respondents in the research location are limited. For accuracy reason, all population in the sub district of South Dolo were chosen as the sample and it is categorised as cencus approach. Therefore, there are 77 people were chosen as respondents. The findings are analysed by using descriptive analysis with the help of frequency table. The results show that the implementation of village fund allocation in the sub district of south Dolo have been managed in accountable and transparent way. Even though, the application of the principle of accountability at this stage is limited on the physical accountability, the administration has not been fully carried out perfectly because it has not been fully comply with the provisions. The main constraints are the local government official and human resource competencies have not been optimalized. Thus, the assistantship from local government officials is required on an ongoing basis.